Protein molecular structures in alfalfa hay cut at three stages of maturity and in the afternoon and morning and relationship with nutrient availability in ruminants. (29th April 2013) - Yari, Mojtaba; Valizadeh, Reza; Naserian, Abbas Ali; Jonker, Arjan; Yu, Peiqiang
Abstract BACKGROUND Molecular structures in feed protein influence its digestive behavior, availability and utilization. From a nutritive point of view, stage of maturity and cutting time are important factors affecting nutrient profiles and availability of alfalfa (Medicago sativa L.) hay in ruminants. The objectives of this study were to determine protein molecular structures by Fourier transform infrared spectroscopy (FTIR), and their relationship with nutrient profiles and availability in ruminants of alfalfa hay cut at early bud, late bud and early flower stages and in afternoon and morning. RESULTS With advancing maturity, molecular structure ratios of α‐helix:β‐sheets decreased, while amide I:amide II increased (P ≤ 0.05). Alfalfa cutting in afternoon versus morning increased protein structure α‐helix:β‐sheets and α‐helix:others ratios (P < 0.05) and tended to decrease the proportion of β‐sheets (P = 0.09). Positive correlations were found for α‐helix:β‐sheet ratio (R ≥ 0.60; P < 0.05) with intermediately degradable protein (PB2) and ruminal degradability and intestinal protein supply, and all these parameters correlated negatively with amide I:amide II ratio (R ≤ −0.62; P < 0.05). CONCLUSION Protein molecular structures in alfalfa hay changed with advancing maturity and during the day and these protein structures affected predicted nutrient availability of alfalfa hay in ruminants. © 2013 Society of Chemical Industry